Folic acid as ultimate in disease prevention: Folate also improves mental health (BMJ Publishing Group, 2004)

(untitled)
Folate also improves mental health EDITOR—Lucock considered the likely effects of mass use of folate but did not mention the potential benefits to mental health.1 Associations between folate status and mood have been known for some time, with folate deficiency considered a treatable cause of depression. Emerging evidence from randomised trials shows that the augmentation of conventional antidepressant treatments with folate may improve outcome, and this effect may be seen even in patients with normal folate concentrations at baseline.2 Observational studies also find associations between folate status and dementia,3 although currently trials of dietary supplementation are not conclusive.4 The effects on health of fortification with folate may not be limited to birth defects, vascular disease, and cancers.